Cross-Cultural Communication: The Role of Culture and Barriers in Intercultural Interaction - Ahmad, Amal hidayat; Ahmadin, Ahmadin; Ibrahim, Ibrahim (Jurnal Ilmiah Mandala Education (JIME), 2026)
Cross-cultural communication has become an important aspect of social interaction in the era of globalization, as it allows individuals from different cultural backgrounds to understand each other and establish harmonious relationships. The research method uses a literature review, where this research uses scientific journals as a basis. This paper discusses verbal (language and accent) and nonverbal communication (gestures, distance, eye contact, and body language), differences in high-context and low-context communication styles, and communication barriers such as stereotypes, prejudices, and misunderstandings. The analysis shows that the effectiveness of cross-cultural communication depends not only on language skills, but also on cultural awareness, empathy, and the ability to adapt to social norms and nonverbal behavior. Developing effective communication competencies allows individuals to interact more productively, reduce conflict, and appreciate cultural diversity.